EKSPERIMEN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA KERANJANG BIJI-BIJIAN TERHADAP HASIL BELAJAR MATERI PERKALIAN DAN PEMBAGIAN SISWA KELAS II SDN SAPTORENGGO 02 - Amanda Purwandari; Dyah Tri Wahyuningtyas (Jurnal Ilmiah Sekolah Dasar, 2017)
Learning math using rote memorization, making it difficult students understand the basic concepts of multiplication and division. Students also thought that mathematics is a difficult subject and tedious, because teachers rarely use the model of learning and use of media only using the environment around students. This study aims to determine whether there is any difference in learning outcomes of students who use and do not use media-assisted learning model TGT grain basket. This study uses a quantitative approach with experimental methods and research design quasi experiment. This research sample that is grade II totaling 50 students and consists of two classes. The results of this study were tested using paired samples t test and obtained t of 5.057 while t table (sig. 0.05 and df = 23) of 2.069 which indicates thitung greater than ttable namely: 5.057> 2.069 which means that H0 rejected and Ha accepted. So it can be concluded that there is a significant difference between the results of student learning to use and not use the media-assisted learning model TGT grain basket.Â